Whey Protein Isolate Supplementation While Endurance Training Does Not Alter Cycling Performance or Immune Responses at Rest or After Exercise - Forbes, Scott C.; Bell, Gordon J. (Frontiers in Nutrition, 2019)
This study examined whey protein isolate supplementation combined with endurance training on cycling performance, aerobic fitness and immune cell responses. Eighteen male cyclists were randomly assigned to either placebo (PLA) or whey protein supplementation (WS; 1.0 g·kg body mass−1·d−1 in addition to their dietary intake). Both groups completed the identical endurance training program, 4 days per week for 6 weeks. Blood samples were obtained at rest and after 5 and 60 min of recovery from a simulated 40 km cycling time trial (TT) and were repeated after training. Baseline dietary intake of protein prior to supplementation was 1.52 ± 0.45 and 1.46 ± 0.44 g·kg body mass−1·d−1 for the WS and PLA groups, respectively. There were similar improvements in TT performance (WS: 71.47 ± 12.17 to 64.38 ± 8.09 min; PLA: 72.33 ± 12.79 to 61.13 ± 8.97 min), and peak oxygen uptake (WS: 52.3 ± 6.1 to 56.1 ± 5.4 mL·kg−1·min−1; PLA: 50.0 ± 7.1 to 54.9 ± 5.1 mL·kg−1·min−1) after training in both groups. White blood cells (WBC) and neutrophil counts were elevated 5 min after the TT and further increased after 60 min (P < 0.05). The exercise-induced increase in WBC and neutrophil counts at 5 and 60 min after the TT were attenuated after training compared to before training (P < 0.05). Lymphocytes increased 5 min after the TT and decreased below rest after 60 min of recovery (P < 0.05). Following training lymphocytes were lower after 60 min of recovery compared to before training. There was no change in natural killer cell activity with exercise, training or between groups. It was concluded that whey protein isolate supplementation while endurance training did not differentially change cycling performance or the immune response at rest or after exercise. However, endurance training did alter performance, aerobic fitness and some post exercise immune cell counts.